Estudio de factibilidad técnico-financiera del uso de energía solar térmica como sustituto de combustible en la generación de vapor para inyección continua en un campo de estudio (2017)
A simulation was carried out for the evaluation of the model and performance of the solar thermal energy technologies in the field of study and the results of the simulation were analyzed for the estimation of the increase of the production of heavy crude according to the generation of steam for continuous injection that provides the use of solar thermal energy.